1993
DOI: 10.1177/0265407593101004
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Distress Following Heterosexual Relationship Dissolution

Abstract: The purpose of this study was to examine correlates of initial distress and current recovery among individuals who have experienced the breakup of a dating relationship, including factors associated with commitment to the relationship (i.e. satisfaction, duration, closeness, perceived alternatives) and factors associated with coping with life stressors (i.e. perceptions of the controllability of the breakup, social support and self-esteem). Participants were 34 males and 51 females who had experienced the brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
101
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 9 publications
7
101
0
Order By: Relevance
“…Time since breakup was associated with distress and adjustment in several studies (Field et al, 2009;Frazier & Cook, 1993;Locker et al, 2010). Even in this study, distress decreased between T1 and T2 regardless of group assignment.…”
Section: Hypothesis Imentioning
confidence: 96%
See 1 more Smart Citation
“…Time since breakup was associated with distress and adjustment in several studies (Field et al, 2009;Frazier & Cook, 1993;Locker et al, 2010). Even in this study, distress decreased between T1 and T2 regardless of group assignment.…”
Section: Hypothesis Imentioning
confidence: 96%
“…In a longitudinal study, Fine and Sacher (1997) found that couples who at Time I had higher commitment level and lower perceptions of alternative relationships were more likely to experience significant distress after their breakup. Frazier and Cook (1993) further broke down the components of commitment, examining satisfaction, duration, closeness, and perceived alternatives as facets of commitment. More satisfaction, longer duration, perceived closeness, and less perceived alternatives pre-dissolution once again predicted distress.…”
Section: Relationship Dissolutionmentioning
confidence: 99%
“…In terms of gender, it is not clear whether men or women fare differently with respect to their psychological adjustment after a non-marital relationship ends (for a consideration of marriage, see Kiecolt-Glaser & Newton, 2001). Although most studies report no gender differences in distress after a break-up (Frazier & Cook, 1993;Helgeson, 1994;Simpson, 1987;Sprecher, 1994), findings from the Boston Dating Couples Study indicated that at the 1-year follow-up of 15 couples who ended their relationship, men reported feeling more depressed, lonely, less happy, and less free after the break-up than their female partners. Mearns (1991) surveyed a more representative sample of 583 undergraduates who experienced a break-up after an average of 10-months dating and found that women reported significantly more depression following the end of the relationship (see also Monroe et al, 1999).…”
Section: Consequences Of Relationship Deteriorationmentioning
confidence: 99%
“…In their prospective epidemiological investigation of the onset and recurrence of major depressive disorder (MDD) in adolescence, Monroe et al (1999) found that the recent break-up of a romantic relationship was a specific and unique risk factor in the onset of MDD. For young adults, the severing of romantic bonds also is associated with depression, as well as anxiety, prolonged longing for an ex-partner, and interferences with daily routines (Feeney & Noller, 1992;Fine & Sacher, 1997;Frazier & Cook, 1993;Hill, Rubin, & Peplau, 1976;Sprecher, 1994;Simpson, 1987).…”
Section: Consequences Of Relationship Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation